Anaesthesia mumps after laparoscopic right hemicolectomy under general anaesthesia: A case report. (March 2021) - Liu, Yu-Hong; Pu, Ta-Wei; Yu, Hsing-Wei; Kang, Jung-Cheng; Hsiao, Cheng-Wen; Chen, Chao-Yang
Highlights: Images of the patient neck and buccal mucosa were taken when symptoms first appeared. The images on the following 3 days show the neck swelling to have subsided. To the best of our knowledge, we present the first case of anaesthesia mump after surgery of colectomy. Abstract: Introduction: Anaesthesia mumps is an extremely rare postoperative complication that occurs following various surgical procedures after general anaesthesia. We aimed to contribute to the growing knowledge of potential clinical presentations, outcomes, and possible causes. Presentation of case: A 93-year-old man experienced acute swelling of a unilateral parotid gland 1 day after laparoscopic right hemicolectomy under general anaesthesia. The symptoms he presented with were acute, non-tender swelling in the left preauricular and submandibular triangle with well-marginated, circular swelling of the buccal mucosa. Amylase level was within the normal range. Computed tomography showed left preauricular soft tissue swelling and enlargement and an enhanced left parotid gland exhibiting inflammation. The swelling subsided after 3 days of conservative treatment. Discussion: Anaesthesia mumps have been associated with a variety of surgeries, including colorectal surgery, and is a rare complication after the induction of general anaesthesia. Despite the few cases presenting with airway obstruction, the outcome for swelling of the parotid or submandibular gland is generally good. Conclusion: Early awareness of anaesthesia mumps and close evaluation lead to a fair prognosis for scar presentation.